Seismic anomalies in stable continents: exploring earthquake clusters and hidden faults in Southern Africa - Whitehead, Benjamin (Department of Geological Sciences, 2025)
In southern Africa many earthquake clusters cannot be associated with faults and, con-versely, known major fault scarps often have no observed earthquake clusters. One example is the Hebron Fault Scarp (Chapter 2), a major neotectonic scarp which has no associated earthquake cluster reported in regional catalogues. In this study a seismic deployment was done at the fault and it is shown that microseismic activity does occur below the detection limits of regional networks. In contrast, the Leeu-Gamka Earthquake Cluster (Chapter 3) occurs without any observable surface rupture. Here, ambient noise tomography was done to generate Rayleigh wave group velocity maps which show a ve-locity transition across the lineament defined by the trend of earthquakes. This velocity transition is interpreted as evidence for displacement on a fault, which is not readily ob-servable at surface. It is argued that the apparent disparity between earthquake clusters and fault scarps observed in southern Africa is a result of insufficient seismic network coverage and incomplete identification of active faults. Therefore seismic hazard assess-ments would benefit from both denser regional seismic network deployments and more detailed geological mapping to identify potentially hazardous, active faults. With the exception of incipient branches of the East African Rift, most of southern Africa is located in a stable continental region, geographically far removed from active tectonic plate boundaries. Nevertheless the region is experiencing ongoing seismicity, often in transient clusters rather than along lineaments. The distance of these earthquakes to plate tectonic boundaries raises questions about the mechanism leading to crustal stress release. A “steady-state” stress accumulation model may apply, where faults are con-tinuously loaded until the fault strength is exceeded. Alternatively an “ambient stress” model may be appropriate, where dormant ambient stress is released by either fault weakening or by transient stress perturbations. These models are not mutually exclu-sive. The steady-state model implies that repeat events should occur on active faults, but with longer recurrence times than at plate boundaries, while the ambient stress release model suggests that seismicity migrates to other regions once a rupture occurs and that triggering by natural or anthropogenic changes in overburden or fluid pressure may play an important role. The validity of these models is addressed by reviewing earthquake catalogues and investigating prehistoric fault scarps, some of which show evidence for repeat-ruptures on single scarps (Chapter 4). Finally, selected fault scarps in the region are investigated (Chapter 4) and fault scaling relationships are used to demonstrate that large earthquakes with magnitudes > M W 7 may occur rarely. Although these magnitude estimates should not be seen as exact, in many cases they are up to two units of magnitude larger than estimates of maximum pos-sible magnitude in previously published probabilistic seismic hazard assessments. This discrepancy is attributed to the sensitivity of probabilistic estimates of maximum possi-ble magnitude to the maximum known magnitude, combined with difficulty in obtaining pre-instrumental data. It is suggested that the assessments are updated to include new large pre-instrumental earthquakes as these become available.